FAKTOR-FAKTOR YANG MEMPENGARUHI STRUKTUR MODAL PADA PERUSAHAAN SUBSEKTOR PROPERTY DAN REAL ESTATE YANG TERDAFTAR DI BURSA EFEK INDONESIA - Dara, Siti Ruhana; Mariah, Mariah (Economic Faculty, Attahiriyah Islamic University, 2018)
The purpose of this study is to examines the antesedents of capital structure. The object is 42 companies in the property and real estate sub-sectors listed on the Indonesia Stock Exchange (IDX) in 2015-2017 periods. Regression analysis was used to test the hypothesis. The results showed that the firm size variable had a significant effect on the capital structure, the profitability variable had a significant effect on the capital structure while the asset structure variable had no effect on the capital structure. And together with company size variables, profitability and asset structure affect the capital structure. Keywords: Profitability, Asset Structure, Capital Structure